2017
DOI: 10.1039/c6nr07975j
|View full text |Cite
|
Sign up to set email alerts
|

Highly thermal-stable paramagnetism by rolling up MoS2nanosheets

Abstract: Controlling phase transitions through local strain engineering is an exciting avenue for tailoring the electronic and magnetic properties of materials at the nanoscale. Herein, we demonstrate a tunable semiconducting to metallic phase transition of two-dimensional transition metal dichalcogenides using strain engineering through rolled up MoS sheets (named as MoS scrolls). A phase incorporated structure for MoS nanoscrolls containing the maximum concentration of 1T phase (∼58%) with high thermal stability up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 36 publications
1
42
0
Order By: Relevance
“…Recently, there have been studies exploring controllable methods for the fabrication of wrinkles, folds, and scrolls on TMD materials 56‐58,69‐73 . The preparation of wrinkled TMD structures often involves the transfer of the TMDs to a pre‐stretched polymer or rigid substrates with pre‐defined microstructures and thermally induced polystyrene (PS) substrate 56‐58,74‐84 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there have been studies exploring controllable methods for the fabrication of wrinkles, folds, and scrolls on TMD materials 56‐58,69‐73 . The preparation of wrinkled TMD structures often involves the transfer of the TMDs to a pre‐stretched polymer or rigid substrates with pre‐defined microstructures and thermally induced polystyrene (PS) substrate 56‐58,74‐84 .…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of folded TMDs also occurs during sample exfoliation and transfer 69,86‐88 . Limited by the sample size, mechanical property, and chemical stability, 89 the self‐assembly of scrolls requires an external medium, such as a weak argon plasma and treatment with a drop of alcohol 70‐73 . Such topological TMD structures greatly affect the optical properties of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, another finding revealed that 1T‐MoS 2 nanotubes could be prepared through a rolling process with the gliding of 2H‐MoS 2 nanosheets by its inner atomic plane . As shown in Figure b, the S‐plane during the rolling up of the 2H‐MoS 2 nanosheets is glided over a distance equivalent to a = 3.16 Å.…”
Section: Crystal Structures and Morphologies Of Tmdcsmentioning
confidence: 95%
“…b) Schematic presentation of synthesis of the 1T metallic phase. Reproduced with permission . Copyright 2017, The Royal Society of Chemistry.…”
Section: Crystal Structures and Morphologies Of Tmdcsmentioning
confidence: 99%
“…Only a few previously published articles involved fabricating the NSs. Moreover, the reported processes are complicated, and the conversion yield is tiny limiting their application 16 23 . Up to date, there is no general and efficient method to enable assembling the NSs with high-yield.…”
Section: Introductionmentioning
confidence: 99%